(untitled) (Confluenţe Bibliologice, 2023)
Răzvan Theodorescu in his „Studii Brâncovenești / Brâncovenești Studies", reflects some representative passages about the reign of Constantin Brâncoveanu from a historical, cultural and artistic aspect. The ambition of this text is to draw attention to the personality of Constantin Brâncoveanu is highlighted in the religious and residential architecture, in the mural painting.